Focal Atrial Tachycardia Surrounding the Anterior Septum: Strategy for Mapping and Catheter Ablation. (June 2015) - Wang, Zulu; Ouyang, Jinge; Liang, Yanchun; Jin, Zhiqing; Yang, Guitang; Liang, Ming; Li, Shibei; Yu, Haibo; Han, Yaling
Abstract : Background—: Focal atrial tachycardias (ATs) surrounding the anterior atrial septum (AAS) have been successfully ablated from the right atrial septum (RAS), the aortic cusps, and the aortic mitral junction. However, the strategy for mapping and ablation of AAS-ATs has not been well defined. Methods and Results—: Of 227 consecutive patients with AT, 47 (20.7%; mean age, 56.3±11.6 years) with AAS-ATs were studied; among them, initial ablation was successful at RAS in only 5 of 14 patients and at noncoronary cusp (NCC) in 28 of 33 patients. In 45 of the 47 patients, the 46 of 48 AAS-ATs were eliminated at RAS in 8 patients, NCC in 35 patients (earliest activation time at NCC was later than that at RAS by 5–10 ms in 6 patients), and aortic mitral junction in 3 patients (all with negative P wave in lead aVL and positive P wave in the inferior leads), including 1 patient whose 2 ATs were eliminated separately from the NCC and the aortic mitral junction. Conclusions—: Most of the ATs surrounding the AAS can be eliminated from within the NCC, which is usually the preferential ablation site. Ablation at the RAS and aortic mitral junction should be considered when supported by P-wave morphologies on surface ECG and results of activation mapping and ablation.